2017
DOI: 10.14393/rbcv69n6-44315
|View full text |Cite
|
Sign up to set email alerts
|

Análise Dos Incêndios Ocorridos No Parque Nacional Da Chapada Diamantina-Bahia Em 2008 E 2015 Com Suporte Em Índices Espectrais De Vegetação

Abstract: A ocorrência de incêndios na vegetação em áreas protegidas constitui uma das graves ameaças à conservação da biodiversidade nestas áreas. O Parque Nacional da Chapada Diamantina (Bahia) se inclui entre as Unidades de Conservação com maior quantidade de focos de incêndios do Brasil. Neste sentindo, a presente pesquisa propõe-se a identificar as áreas acometidas por incêndios nos anos 2008 e 2015, dentro da extensão do Parque, utilizando os índices espectrais NBR e NDVI, visto que nesses anos ocorreram os últim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Following this trend, the re-establishment of vegetation cover observed in the present study also occurred in a short period (16 to 20 months) (Araújo & Conceição, 2021), which corroborates the results found with the application of the NBR index. Leite et al (2017) sought to identify fire-affected areas in 2008 and 2015 and compare the effectiveness of both NBR and NDVI spectral index for the same area as this study. The authors found that NBR attributed negative values to burned areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this trend, the re-establishment of vegetation cover observed in the present study also occurred in a short period (16 to 20 months) (Araújo & Conceição, 2021), which corroborates the results found with the application of the NBR index. Leite et al (2017) sought to identify fire-affected areas in 2008 and 2015 and compare the effectiveness of both NBR and NDVI spectral index for the same area as this study. The authors found that NBR attributed negative values to burned areas.…”
Section: Discussionmentioning
confidence: 99%
“…When the response is close to zero, the reflectance of both bands 5 and 7 are approximately equal, as with clouds, unproductive vegetation, bare soil, and rock outcrop. On the other hand, when NBR is negative, the reflectance in band 7 is higher than in band 5, suggesting high water stress on plants and the negative values representing burned areas (Leite et al, 2017;Santos et al, 2020).…”
Section: Processing In Google Earth Enginementioning
confidence: 96%
See 1 more Smart Citation